Prevalence of Musculoskeletal Disorders among Housewives in Lahore: Cross Sectional Study - Siddique, Mehwish; Jabbar, Mehreen; Zulfaqar, Nimra; Aslam, Zubair; Riasat, Hunza (Pakistan Journal of Medical & Health Sciences, 2022)
Housewives are always at high risk of musculoskeletal disorders due to their daily life activities. Musculoskeletal disorders commonly experienced by housewives can affect their health and well-being. Aim: To find out the prevalence of musculoskeletal disorders among housewives in Lahore. Study Design: Cross sectional study. Methodology: A questionnaire survey was carried out among 179 housewives through convenient sampling technique residing in Lahore. The Nordic questionnaire was used for data collection. Data was collected through a semi structured questionnaire including closed ended questions regarding pain and disability. Statistical analysis: The collected data was analyzed by using SPSS version 25. Results: There was high prevalence musculoskeletal problems in last 7 days and 12 months, at least one region of the body’s involved in musculoskeletal disorders. Housewives in the age range of 31 to 40 were mostly (57%) overweight faced the severity of pain in neck (54.2%), lower back (45.3%), hips (21.8%), knees (30.7%),and in ankle (30.7%).The severity of functional impairment in last 12 months was more in lower back region (60.3%). While in the neck region was 45.8%. Conclusion: It was concluded that prevalence of musculoskeletal disorders was higher in one or more than one region in last 7 days and 12 months than functional impairment in last 12 months.